Hydrochloric acid (HCl) in the stomach: proposing a simple and low-cost practical class for the simulation of physiological aspects of digestion in the discipline of Biology (Research, Society and Development, 2021)
Nowadays, more than ever, the teacher is constantly challenged in educating students using, in addition to theoretical classes, the proposal and execution of practical classes. Thus, in the discipline of Biology, experimental classes are of great importance in the teaching and learning process, as they allow to apply in practice what has been learned in theoretical classes, and instigate the perspective of scientific experimentation, facilitating the learning of students. In this sense, using simple and low-cost materials, the main objective of this article is to propose an experimental class in order to facilitate the learning of students in the discipline of Biology in High School, regarding the mechanism of protein digestion Human stomach physiology, in addition to aspects related to the protection of the gastric mucosa in the presence of hydrochloric acid (HCl). Thus, with the realization of this experimental class, we believe that students can contextualize the learning of the proposed theme in a more effective way, in addition to making scientific experimentation more present within the school environment.